Acts of God: Continuities and change in Christian responses to extreme weather events from early modernity to the present. (13th December 2019) - Hardwick, Joseph; Stephens, Randall J.
Abstract: Scholars, activists and others increasingly acknowledge that religion—whether conceived in terms of ideas, rituals or institutions—can help us cope with climate change and make sense of extreme weather events. Churches provide moral lessons in times of crisis, they spread awareness of climate change and, through community ritual, religious institutions can nurture a sense of collective responsibility. Much has been written on how contemporary faith groups have understood and acted on climate change and extreme weather events. Yet this literature is often not historically rooted and makes only superficial reference to the complex relationships between climate, extreme weather and religion in the past. Without an historical awareness we cannot understand the extent to which present‐day religious discourses on the environment—from those articulated by "greener faith" advocates to fundamentalist skeptics—connect with how past societies understood climate and, more specifically, extreme weather events. A survey of the literature on Christian responses to extreme weather events, whether these be slow disasters (droughts) or isolated events (storms), suggests that histories that emphasize ruptures in attitudes to the natural world are problematic. Extreme weather events have long been regarded as omens and signs, and as divine judgments on sin. It is still thought that weather disturbances reflect disorders in human society. This literature survey introduces these continuities in Christian responses to extreme weather by ranging broadly across the English‐speaking world from early modernity, though special attention is given to current work on Anglophone settler societies. This article is categorized under: Climate, History, Society, Culture > Ideas and Knowledge Abstract : Preacher and men praying for rain, Queensland, c. 1900, John Oxley Library, State Library of Queensland, Accession number: D6‐4‐85. Retrieved from https://trove.nla.gov.au/work/36931612?q=praying+rain&c=picture&versionId=47948392